Subordinate Compound Sentence Patterns in Juicy Luicy Song Lyrics - Putri, Leora Salsabilla Prastyana (Bahasa Indonesia Prima, 2025)
This research aims to analyze the use of subordinative compound sentences in Juicy Luicy song lyrics. This research focuses on identifying subordinative conjunctions used in song lyrics to strengthen the messages and emotions conveyed. The method used is descriptive qualitative with content analysis approach to identify and categorize subordinative compound sentences based on the relationship between clauses such as cause-effect, time, purpose, and condition. The data used are the lyrics of Juicy Luicy songs that are officially published. The results show that subordinate compound sentences play an important role in clarifying the relationship between clauses and deepening the meaning of the lyrics. The use of subordinate compound sentences is effective in enriching emotional expressions and messages to be conveyed in songs. This research provides new insights into the role of sentence structure in conveying messages through music.